Gastrografin can be detected in ex vivo biological specimens by dual‐energy CT scanning. Issue 5 (15th June 2020) - Clark, David A; Yeoh, Edward; Edmundson, Aleksandra; Pratap, Jit; Snow, Tom; Solomon, Michael; Coucher, John
Abstract: Background: Dual‐energy CT is able to distinguish between materials based on differences in X‐ray absorption at different X‐ray beam energies. The strong k‐edge photoelectric effect of materials with a high atomic number makes this modality ideal for identifying iodine‐containing compounds. We aim to evaluate dual‐energy CT for the detection of Gastrografin (GG) (diatrizoate, Bayer PLC, Reading, UK) enteric contrast medium and validate the conditions for the measurement in ex vivo samples. Methods: Dual‐energy CT acquisitions were performed to detect Gastrografin in serial dilutions of water, saline and body fluids. We also evaluated the stability of Gastrografin solutions over time at room temperature. Stool specimens were examined to validate the proposed study protocol for clinical applications. Results: Concentrations as low as 0.2% of Gastrografin were reproducibly detected in vitro and ex vivo samples by DECT, with linear readings ranging from 0.2% to 25% Gastrografin. Gastrografin was shown to be stable in ex vivo biological samples, and there was no difference in detection over time. Gastrografin was detected in stool specimens when administered orally. The detection curves followed the expected saturation effect at high concentrations of iodine. Conclusions: Dual‐energy CT offers a convenient, quick, reliable and reproducible method for detecting and quantifying the presence of Gastrografin in ex vivo clinical specimens. Biological solutions containing Gastrografin are stable over time. A minimum dilution level of 25% is suggested to avoid beam saturation and inaccurate results.